Horticultural pilotproject of the social economy in Szigetmonostor - Orosz, György; Emődi, Andrea; Hartman, Mátyás (JOURNAL OF LANDSCAPE ECOLOGY, 2014)
The Strategy of „Eco Island of Szentendre was developed in the spring of 2012. This strategy consisted of a project aiming the creation of a horticulture maintained by the social economy of the Local Government. In this study we determined the project scope and the detailed concept at Szigetmonostor. The feasibility study contains the selection of the territory, the needs of the public kitchen, the main plans of the horticulture with maintenance and economic calculations, and with the investment needs for preservation. During planning we focused on environmental and ecological management, healthy food production and protection of groundwater resources.
Keywords: Island of Szentendre; protection of groundwater resources; agriculture; horticulture; local products; social econom; self-sufficiency